MINIMNYA LITERATUR DI ERA DIGITAL PADA REMAJA (USIA 12-18 TAHUN) - Tranggono Tranggono; Syava Nur Qolbiyah Niswan; Purwasih Diansiwi; Muhammad Pradana Alif Gustama; Yasmin Nuwwara Khalisha; Risma Zuhriyatun Nasihah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The presence of the digital era has brought very important changes in life. The ease of access to technology has created dependence on gadgets, especially among teenagers. Even though the digital era has many positive impacts, the negative impacts are more dominating. The easy access to the internet makes teenagers lulled so that they have little intention of being literate. In addition, there is a lack of reading space that is suitable for the condition of teenagers. This article aims to determine literacy interest in adolescents in the current digitalization era. How is the impact given and solutions that can overcome these problems. This research uses several supporting methods such as surveys, case studies, document analysis, group discussion forums and content analysis. Interest in reading among adolescents has decreased over time, so through this article a simple library design is presented to support literature for adolescents with a comfortable concept